Investigation of rare sequence variants in putative susceptibility genes for schizophrenia and autism spectrum disorders - Furlong, Sarah (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2013)
Schizophrenia (SZ) and Autism Spectrum Disorders (ASD) are complex neuropsychiatric disorders that have a very large health, societal and economic burden in Ireland. They affect approximately 1% and 0.8% of the population respectively, with heritability estimated to be as high as 80%. The underlying genetic architecture and pathogenesis of each disorder remains to be elucidated. Substantial phenotypic and genetic overlap exists between SZ and ASD, indicating that they may share a common pathogenic mechanism. The aim of this study is to identify rare variants that contribute to the pathophysiology of SZ and ASD.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin